EKSTRAK DAUN KELOR (Moringa oleivera) SEBAGAI ALTERNATIF UNTUK MENURUNKAN KADAR GULA DARAH PADA MENCIT - Radiansah, Roy; Rahman, Nurdin; Nuryanti, Siti (Jurnal Akademika Kimia, 2013)
Moringa is a plant use as a traditional medicine. The leaves of moringa (moringa oleivera) is part of the plant that could reduce the blood sugar levels. This research aims to determine the extract (infusion) of moringa leaves (moringa oleivera), to reduce the blood sugar level in mice and to determine the most effective concentrations of moringa leaves extract (infusion) to reduce the blood sugar levels in diabetic mice. Bioactifive compounds of moringa leaves was identified by using reagent dragendorff to test alkaloids while reagent chloroform, acetic anhydride and sulfuric acid to test steroids/terpenoids. The study was a clinical trial by using animal testing, 15 mice which was divided to 5 group of treatments: P1 (food + EDTA + glucose, 10% of moringa leaves infusion, Na-CMS), P2 (food + EDTA + glucose, 20% of moringa leaves infusion, Na-CMS), P3 (food + EDTA + glucose, 40% of moringa leaves infusion, Na-CMS), P4 (food + EDTA + glucose, glibenklamid, Na-CMS), and P5 (food + EDTA + glucose, Na-CMS). Blood glucose levels measured with GlukoDr instrument. The measurement data was analyzed by ANOVA test with the 95% confidence level followed by Duncan test to determine the significant different of each treatment to obtained the significant data. The result showed that moringa leaves extract consist of alkaloid and steroid which plays an important role to reduce blood sugar level and the concentration of the moringa leaves extract 20% was effective to the reduce the blood sugar level of diabetic mice.